Pengaruh Sumberdaya Takberujud pada Kinerja Organisasional: Pendekatan Komplementarian - Fairuzzabadi Fairuzzabadi (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2011)
AbstractThe study aims to examine the impact of a set of independent intangible organizational resources (managerial capabilities, human capital, perceived organizational reputation, internal auditing, organizational culture, relational capabilities and labor relation) and their interactions on the organizational performance in a sample of private higher education in Yogyakarta. The regressions results indicated organizational performance in the dimension of organizational effectiveness can be well-explained by set of intangible organizational resources, excluding labor relation. The results also indicated the interactions among human capital with organizational culture and labor relations, perceived organizational reputation and internal audit, and between organizational culture and relational capabilities had compensatory effect or interference interaction in explaining performance of higher education institution.Keywords:Intangible Resources, Organizational Performance, Complementarities, Higher Education InstitutionAbstrakPenelitian ini bertujuan untuk menguji pengaruh sekumpulan sumber daya takberujud (kapabilitas manajerial, modal manusia, reputasi organisasional persepsian, pengauditan internal, budaya organisasional, kapabilitas relasional dan hubungan ketenagakerjaan) serta interaksi antar sesamanya terhadap kinerja organisasional institusi pendidikan tinggi swasta di Yogyakarta. Hasil penelitian ini menunjukkan bahwa kumpulan sumberdaya takberujud merupakan prediktor utama bagi kinerja organisasional, kecuali hubungan ketenagakerjaan. Lebih lanjut, hasil penelitian ini juga menunjukkan bahwa interaksi antara modal manusia dengan budaya organisasional dan hubungan ketenagakerjaan, reputasi organisasional persepsian, dan interaksi antara budaya organisasional dengan kapabilitas relasional memiliki hubungan yang saling menggantikan (compensatory effect) atau interference interaction di dalam menjelaskan variansi kinerja organisasional institusi pendidikan tinggi. Kata Kunci:Sumberdaya Takberujud, Kinerja Organisasional, komplementarian, Institusi Pendidikan Tinggi.